STUDI LITERATUR: KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DALAM PEMBELAJARAN MATEMATIKA - Yarmayani, Ayu (Universitas Batanghari Jambi, 2026)
This study aims to examine mathematics education research on mathematical problem-solving skills published in SINTA-indexed mathematics education journals from 2022 to 2023. Methodologically, this study uses a qualitative content analysis approach. The analysis was conducted on several main aspects that are the focus of the study. First, based on the research approach, it shows a tendency towards a descriptive qualitative approach. The dominance of the descriptive qualitative approach in this study indicates a strong tendency in mathematics education studies that focus on revealing and measuring problem-solving indicators in depth and context. Second, based on the distribution of research subjects in this study, it shows an uneven trend, where Junior High School students are the most dominant group studied compared to other levels of education. This phenomenon reflects the crucial existence of research that focuses on the phase of cognitive development of students at the SMP level, which theoretically represents a transitional stage from concrete to abstract thinking. Third, based on the distribution of topics, it provides an illustration that studies on mathematical problem-solving skills have been conducted in various material contexts, but there are still opportunities to expand the scope of research, especially on materials that have not been widely explored.